A356 합금의 열처리에 따른 조직변화와 기계적 성질에 관한 연구 - 최병주 (The Graduate School, Ajou University, 2014)
Recently, automotive industry is attempting to replace steels for automotive parts with light-weight alloys such as aluminum alloy, because of the growing regulations of the exhaust gas and the engine effectiveness of a vehicle. Therefore, an investigation was performed to observe the formation of mechanical properties, cause the microstructure deformation, in A356 aluminum parts during the heat-treatment operation. In order to produce an accurate thermal condition of the heating process, a detailed description of the constitutive behavior of A356 is required in the heat-treatment condition. In the past few decades, researches of A356 heat-treatment process have been conducted to improve the properties of the A356 alloy. Particularly, various heating conditions have been studied to achieve the optimized mechanical properties such as ultimate tensile strength, yield strength and elongation. On the other hand, studies which related with the microstructure and mechanical properties are seldom conducted for the A356 manufacturing process than each different research. In this study, the microstructure variation and enhanced mechanical properties of the heat-treatment process are studied to choose the optimal heating condition with low energy consumption and high productivity. The results include the following: First, the selection of the heat-treatment condition by the literature review, a solution treatment at 530℃ for 4hours, followed by water quenching, and aging treatment at 135℃ for 3hours were selected. Second, the observation of the microstructure variation, which uses the Scanning Electron Microscope(SEM) to monitor the image of the structure, is researched. As a result, the heat-treated A356 strength can be improved by the observation of the image analysis, because of the characteristic of the Dendrite Arm Space(DAS), A356-F is 64.6 ㎛, A356-T6 is 48.5 ㎛ respectively. Third, mechanical properties are researched to analyze the tensile test. Mechanical properties stronger than American Society for Metals International data(Yield strength 207 ㎫, Tensile strength 283 ㎫, Elongation 12%). The yield strength 237 ㎫, tensile strength 297 ㎫ and elongation 9.3% are obtained about the heated A356. Fourth, the S-N curve is obtained by using the ultrasonic fatigue test. In the result, the fatigue strength of the heat treatment A356 is improved more than casting A356. And their improved strength ratio of the heat treatment process is 44.9%, improved strength ratio of the casting process is 25.4%. Finally, the fatigue analysis is conducted according to the A356 parts manufacturing process, because of the comparison of test and analysis about the fatigue life. Consequently the fatigue analysis and experiment are well matched.
학위논문(석사)--아주대학교 일반대학원 :기계공학과,2014. 2
Keywords: A356; Heat treatment; Microstructure; Tensile test; Fatigue test; Fatigue analysis